An exploration of the problem representations constructed within the South African National Drug Master Plan 4th Edition (2019-2024), for a more nuanced understanding of the challenges and opportunities for harm reduction strategies in South Africa - Maunye, Sibahle (Department of Political Studies, 2025)
This dissertation critically examines problem representations in South Africa's National Drug Master Plan 2019-2024 (NDMP), using Carol Bacchi's (2009) “What's the Problem Represented to be?” methodology. It challenges the conventional framing of the "drug problem" as self-evident, revealing power dynamics and historical influences shaping policy decisions. In the mini-dissertation, tracing the historical evolution of drug policy, from the prohibitionist United Nations International Drug Control Regime (IDCR) to the Addiction-as Disease model and finally recent harm reduction methods, contextualises contemporary problem representations found in the most recent NDMP. This paper the NDMPs representation of people who use drugs (PWUD) being deeply in ingrained historical, racialized tropes. Its emphasis on demand reduction overlooks complex realities and neglects harm reduction strategies which is defined by pragmatic, yet compassionate principles and procedures designed to reduce the harmful effects of risky and dependent drug use. Secondly the NDMP represents society and the economy as a problem because of the complex interplay between substance abuse, gangsterism, and their adverse effects on the economy, contributing to issues of poverty, unemployment, and inequality. Lastly, the NDMP represents institutional capabilities as a problem because of ineffective coordination, governance, and leadership within institutions. Thus, this paper finds that through these representations, the NDMP expresses an intention to shift from prohibition towards public health or human rights strategies, however the complexities the representations it embeds present challenges to the practical and ideological implementation of harm reduction. To address these issues, recommendations put forward in this mini dissertation include a comprehensive NDMP review, direct engagement of policymakers with affected communities, legislative reforms integrating harm reduction, and fostering collaboration among institutions and stakeholders to ensure effective responses. Leadership embracing harm reduction and education against stigmatisation are crucial for a humane and effective response. The path to harm reduction in South Africa necessitates a paradigm shift in policies, perceptions, and practices, striving for inclusivity and compassion reflective of harm reduction principles and reducing the harms associated with substances like Nyaope.